Disability and health-related quality-of-life 4 years after a severe traumatic brain injury: A structural equation modelling analysis. (5th December 2016) - Azouvi, Philippe; Ghout, Idir; Bayen, Eleonore; Darnoux, Emmanuelle; Azerad, Sylvie; Ruet, Alexis; Vallat-Azouvi, Claire; Pradat-Diehl, Pascale; Aegerter, Philippe; Charanton, James; Jourdan, Claire
Abstract: Objectives : To assess predictors and indicators of disability and quality-of-life 4 years after severe traumatic brain injury (TBI), using structural equation modelling (SEM). Methods : The PariS-TBI study is a longitudinal multi-centre inception cohort study of 504 patients with severe TBI. Among 245 survivors, 147 patients were evaluated upon 4-year follow-up, and 85 completed the full assessment. Two outcome measures were analysed separately using SEM: the Glasgow Outcome Scale-extended (GOS-E), to measure disability, and the QOLIBRI, to assess quality-of-life. Four groups of variables were entered in the model: demographics; injury severity; mood and cognitive impairments; somatic impairments. Results : The GOS-E was directly significantly related to mood and cognition, injury severity, and somatic impairments. Age and education had an indirect effect, mediated by mood/cognition or somatic deficiencies. In contrast, the only direct predictor of QOLIBRI was mood and cognition. Age and somatic impairments had an indirect influence on the QOLIBRI. Conclusion : Although this study should be considered as explorative, it suggests that disability and quality-of-life were directly influenced by different factors. While disability appeared to result from an interaction of a wide range of factors, quality-of-life was solely directly related to psycho-cognitive factors.